Isolation and Identification of Bacteria from Some Used Makeup Tools in Sana’a City - Al-Mekhlafi, Nesrain A.; Dahaba, Afnan L. (PSM Microbiology, 2025)
Makeup has become a significant aspect of women's daily lives, and makeup brushes are considered the magic wand for applying makeup to the face. Frequent use and sharing of makeup brushes by different customers may become a potential pathway for bacterial pathogens to spread. The present study aimed to isolate and identify bacterial contaminants in utilized makeup brushes. Twenty makeup tools (brushes and sponges) were collected from different personal houses, student bags, and a beauty salon in Sana’a city, Yemen, and inoculated into two culture media (nutrient agar and blood agar). The identification of isolated bacteria was confirmed by morphology and biochemical characters. The percentage of isolated bacteria in the beauty blender sponges and foundation sponges was higher than in blusher brushes and blending brushes. The bacterial isolates were more prevalent in the shared salon's cosmetic materials than in student bags and personal house cosmetic materials. A total of 50 bacterial isolates were identified as follows: Staphylococcus aureus (42%), Bacillus spp. (24%), Staphylococcus epidermidis (20%), and Bacillus cereus (14%), respectively in utilized makeup brushes. The study has concluded that makeup brushes may act as a source of infection and increase the risk of infection.